Case Report on Hyperuricemia Presenting as One-Sided Disease - Bala, Renu; Srivastava, Amit (Homœopathic Links, 2019)
Hyperuricemia is very common, and a prevalence of up to 15 to 20% has been reported in population-based studies. Although hyperuricemia is not a disease, if uric acid levels remain high, over time they can lead to several diseases. Hyperuricemia is the central risk factor for gout and is a key component of the metabolic syndrome. The case illustrated here is of hyperuricemia with only symptom of pain in the joints, large as well as small, mainly the shoulder joints, knee joints, ankle joints and interphalangeal joints for 2 years without any associated complaint. The case is a one-sided disease, that is, disease in which symptoms are very few, which got cleared up with antisycotic drugs. Thuja and Medorrhinum prescribed in the beginning of the case on the guidelines for one-sided diseases mentioned in Organon of Medicine and later responded very well to Bryonia alba in higher potencies to lower the level of serum uric acid significantly along with long-lasting improvement in signs and symptoms of the patient.
Keywords: hyperuricemia; joint pain; one-sided disease; homoeopathy